Acompañamiento en el final de la vida desde un existencial humanismo - Cabodevilla Eraso, Iosu (Miscelánea Comillas, 2008)
The current society does not offer too many facilities to integrate the death. On the contrary it makes difficult to us not only its experience but also the possibility of living it as a culmination of a lifetime, one of the most disturbing episodes that more intense psychological reactions cause, both in the patient and in their loved ones. The existential-humanism teaches us clearly that if not now, when? If not here where? And if not me, who? The dyings show us that the sense of the illness, pain and death is lived and is explained in the real, daily and small transformation of many lives that are moved and are allowed to feel the pain of the death of other one. In our post-modern West, it is not enough to us to leave us to die, as biological being that we are, but in the same way that we wished a quality of life also we aspired to a quality of death. In the good death keeping ability to decide and to manage own life is important. The accompaniment and support will be essential as it was in other stages of the life cycle. That support will last for the grief period if it was necessary.